2003
DOI: 10.1002/adfm.200390008
|View full text |Cite
|
Sign up to set email alerts
|

Raman Anisotropy Measurements: An Effective Probe of Molecular Orientation in Conjugated Polymer Thin Films

Abstract: Understanding the molecular alignment of conjugated polymers within thin‐film samples is essential for a complete picture of their optical and transport properties, and hence for the continued development of optoelectronic device applications. We report here on the efficacy of Raman anisotropy measurements as a probe of molecular orientation, presenting results for aligned polyfluorene nematic glass films. Comparison is made with the results of optical dichroism measurements performed on the same samples. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 37 publications
4
83
0
Order By: Relevance
“…[25] f(u), the proportion of emitters at an angle, was represented by a normalized 1D Gaussian distribution with a maximum at u ¼ 0 and a standard deviation, s. Fitting for s gave an upper value of 248 for the spread in emissive b-phase molecular orientations about the wire axis. [27] This axial texturing was likely due to mechanical extension of the molecules during solution-assisted template pore filling and, after filling, during solvent evaporation along the pores.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25] f(u), the proportion of emitters at an angle, was represented by a normalized 1D Gaussian distribution with a maximum at u ¼ 0 and a standard deviation, s. Fitting for s gave an upper value of 248 for the spread in emissive b-phase molecular orientations about the wire axis. [27] This axial texturing was likely due to mechanical extension of the molecules during solution-assisted template pore filling and, after filling, during solvent evaporation along the pores.…”
mentioning
confidence: 99%
“…However, the non-zero emission intensity measured at 908 to the wire long axis (VH) indicated that not all of the emissive molecules were perfectly aligned. The spread in molecular orientations relative to the nanowire long axis was estimated from the emission dichroic ratio according to: [25,26] DR…”
mentioning
confidence: 99%
“…4,5 Optical spectroscopy techniques are facile tools for characterizing polymer-based devices [6][7][8] and can be used to probe non-pristine interfaces that are likely to occur in a production environment. 9 In particular, Raman scattering, where the vibrational modes of a molecule are mapped out through the inelastic scattering of light, is capable of elucidating subtle structural and chemical differences in molecular systems and has been successfully utilized to probe important changes 10,11 and degradation effects [12][13][14] in organic thin films and device structures. An extension of Raman scattering is surface-enhanced Raman scattering (SERS) where the plasmonic modes of nanostructured metal are used to enhance the Raman process by several orders of magnitude 15 enabling sensitivities reaching the detection of single molecules.…”
mentioning
confidence: 99%
“…Indeed, orientation affects the intensity of the Raman scattered-light for a given polarization of the incident light [35]. Owing to the smaller pore diameter, uniaxial symmetry is more pronounced for polyaniline obtained in AAO of 45 nm than of 300 nm, so the polymer chains tend to have a preferred orientation (parallel to the AAO walls) [36] thus increasing the intensity of the band at 1167 cm -1 , as observed. To summarize, the spectra of PANI obtained in pores of 300 nm diameter present the same tendency than that of PANI bulk while spectra of PANI obtained in pores of 45 nm illustrate a confinement effect which is not seen in 300 nm.…”
Section: Raman Spectroscopymentioning
confidence: 74%